Transcriptome Analysis of Moso Bamboo (Phyllostachys edulis) Reveals Candidate Genes Involved in Response to Dehydration and Cold Stresses - Huang, Zhuo; Zhu, Peilei; Zhong, Xiaojuan; Qiu, Jiarui; Xu, Wenxin; Song, Li (Frontiers in Plant Science, 2022)
Bamboo (Bambusoideae) belongs to grass family (Poaceae), and has been utilized as one of the most important non-timber forest resources in the world. Moso bamboo (Phyllostachys edulis) is a large woody bamboo with high ecological and economic values. Global climate change bring potential challenge on normal growth of moso bamboo, and therefore the production. Despite the moso bamboo genome has been released, the knowledge on genome-wide responses to abiotic stress is still limited. In this study, we generated a transcriptome data set with respect to dehydration and cold responses of moso bamboo by using RNA-seq technology. The differentially expressed genes (DEGs) after treatments of to dehydration and cold stresses were identified. By combining comprehensive GO enrichment analysis, time-series analysis, and co-expression analysis, candidate genes involved in dehydration responses were identified, which encode ABA/WDS induced protein, late embryogenesis abundant (LEA) protein, 9-cis-epoxycarotenoid dioxygenase (NCED), anti-oxidation enzymes, transcription factors, etc. Additionally, we used PeLEA14, a dehydration induced gene encoding an 'atypical' LEA protein, as an example to validate the function of the identified stress-related gene in tolerance to abiotic stresses, such as drought and salt. We here provided a valuable genomic resource for future excavation of key genes involved in abiotic stress responses and genetic improvement of moso bamboo to meet the requirement for environment resilience and sustainable production.